Eligibility to Use the Fund's Facilities for Concessional Financing : Decisions. (Policy Papers; Policy Paper ;, 2010)
This paper proposes a framework for updating the PRGT eligibility list, based on transparent criteria and a regular review process, including policies for phasing in changes in eligibility. The premise is that access to scarce resources for concessional Fund financing should be preserved for members with a low level of income and related economic and financial vulnerabilities. From this perspective, there are several potential anomalies in the current eligibility list, which has been established primarily on the basis of IDA eligibility, and was last reviewed in 2003.